Communication in crisis. Crisis. FAE in Digital Media Facing COVID-19 - Guerrero Maruri, Fernando (2021)
The present work has been done in COVID-19 time. Its identify lacks in the digital communicational management in the Ecuadorian Air Force, from that, it investigates the situation of the institutions of divergence at the world level and corroborates the general need for a digital plan to deal with crisis and emergency situations. In order to better understand the institutional reality, there are no models of realities external to the one of study that generates an investigative work that crosses institutional publics of digital media, content managers of the case and the authorities that through their decisions influence management social networks. As a final product, an alternative is proposed for the management of institutional social media according to the reality of the Ecuadorian military institution, facing a crisis, which understands and meets particular needs. The final pilot product is a basic input to include in institutional communication plans that determine the need for this type of instrument after the pandemic.